Ecohydrological consequences of tree removal in an urban park evaluated using open data, free software and a minimalist measuring campaign - Deutscher, Jan; Kupec, Petr; Kučera, Aleš; Urban, Josef; Ledesma, José L J; Futter, Martyn (The Science of the total environment, 2019)
With ongoing global climate change and an increasingly urbanized population, the importance of city parks and other forms of urban vegetation increases. Trees in urban parks can play an important role in mitigating runoff and delivering other ecosystem services. Park managers, E-NGOs, citizen scientists and others are increasingly called upon to evaluate the possible consequences of changes in park management such as, e.g., tree removal. Here, we present an unorthodox approach to hydrological modelling and its potential use in local policy making regarding urban greenery. The approach consists of a minimalist field campaign to characterize vegetation and soil moisture status combined with a novel model calibration using freely available data and software. During modelling, we were able to obtain coefficients of determination (R2) of 0.66 and 0.73 for probe-measured and simulated soil moisture under tree stand and park lawn land covers respectively. The results demonstrated that tree cover had a significant positive effect on the hydrological regime of the locality through interception, transpiration and effects on soil moisture. Simulations suggested that tree cover was twice as effective at mitigating runoff than park lawn and almost seven times better than impervious surfaces. In the case of a potential replacement of tree vegetation in favour of park lawn or impervious surfaces an increase in runoff of 14% and 81% respectively could be expected. The main conclusion drawn from our study was that such an approach can be a very useful tool for supporting local decision-making processes as it offers a freely available, cheap and relatively easy-to-use way to describe the hydrological consequences of landcover change (e.g., tree removal) with sufficient accuracy.
Keywords: Urban greenery; stromy; velkoměsta; Hydrology; Open data; Ecosystem; Česká republika; Trees; Green infrastructure; Software; Czech Republic; Parks, Recreational; Conservation of Natural Resources; Cities; zachování přírodních zdrojů; veřejné parky; hydrologie; ekosystém; Ecohydrological services; software; Runoff modelling; Open science